2018
DOI: 10.1038/s41533-018-0100-z
|View full text |Cite
|
Sign up to set email alerts
|

A patient-centric analysis to identify key influences in allergic rhinitis management

Abstract: Allergic rhinitis (AR) is increasingly becoming a patient self-managed disease. Just under 70% of patients purchasing pharmacotherapy self-select their treatment with no health-care professional intervention often resulting in poor choices, leading to suboptimal management and increased burden of AR on the individual and the community. However, no decision is made without external, influencing forces. This study aims to determine the key influences driving patients’ decision-making around AR management. To acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 36 publications
(43 reference statements)
0
30
0
Order By: Relevance
“…To investigate whether patient asthma management behaviour is influenced by having AR, we can start by mapping the asthma health network for people with asthma and AR. We hypothesize that the map will be different to the asthma map defined by Cheong et al and that some of the influences identified in the AR network [21] will appear within the asthma map of those with AR.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…To investigate whether patient asthma management behaviour is influenced by having AR, we can start by mapping the asthma health network for people with asthma and AR. We hypothesize that the map will be different to the asthma map defined by Cheong et al and that some of the influences identified in the AR network [21] will appear within the asthma map of those with AR.…”
Section: Introductionmentioning
confidence: 77%
“…This study used a mixed methods approach based on the theoretical and analytical framework of social network theory as previously developed and utilized by Cheong et al [22] and Cvetkovski et al [21]. Specifically, this study used an egocentric social network framework; it focused on the network of an individual/'ego' (the participant) and the relationships/ 'ties' with individuals or resources/'alters'.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations